PENGEMBANGAN MODUL DIGITAL MULTIMEDIA PEMEBELAJARAN PADA MAHASISWA TEKNOLOGI PENDIDIKAN FAKULAS ILMU PENDIDIKAN UNIVERSITAS NEGERI MAKASSAR - Indah Musfirah MA; Nurhikmah H; Farida Febriati (STKIP Subang, 2024)
The development of this digital module was developed because there are still no digital module learning resources in learning multimedia courses. The problem in this study is the lack of learning resources such as interactive and practical digital modules that support the learning process of both lecturers and students of the Education Technology Study Program at Makassar State University. Therefore, a digital module is needed that can support student learning in the Educational Technology Study Program. This research aims to 1) Describe the level of need for Digital Learning Multimedia Education Modules for Educational Technology Students at the Faculty of Education, Makassar State University, 2) Describe the development design of the Digital Module of Learning Multimedia Education for Educational Technology Students of the Faculty of Education, Makassar State University, 3) Describe the level of validity and practicality of the Digital Module of Learning Multimedia Education for Educational Technology Students of the Faculty of Education, Makassar State University. This research was developed using the 4-D model (Define, Design, Development, Disseminate). The research was conducted at the Educational Technology Study Program, Faculty of Education, Makassar State University. The subjects in this study were 2 validator lecturers (content/material and media), 46 students of the 2020-2022 Educational Technology Study Program, Faculty of Education, Makassar State University. The results of this study indicate that 1) the identification of the level of need for the development of Digital Modules is in the qualification is very much needed, 2) The results of testing the validity of the Digital Module by content / material experts were obtained with a percentage of 86% achievement level in valid qualifications and the results of validation by media experts obtained a percentage of 100% achievement level in very practical qualifications. 3) The results of practicality testing conducted on lecturers of learning multimedia courses with a percentage of 95% which is in very practical qualifications and individual trials consisting of 5 students obtained an average score of 95% which was in very practical qualifications, and large group trials consisting of 22 students obtained an average score of 91% which was in very practical qualifications. Based on the results of this analysis, it can be concluded that the learning resources for Digital Multimedia Learning Modules are valid and practical.